Inclusion from the Inside Out - Buursma, Dirk R. (Journal of religion, disability & health, 2010)
During the late 1980s, the idea of inclusive Christian education came to West Michigan. This article describes one family's journey from self-contained educational programming through a “least restrictive environment” classroom to inclusive education in a Christian day school setting. While acknowledging the challenges and struggles experienced along the way, the story celebrates the results of a determined effort on the part of school administrators, staff, faculty, and the student community to embrace students who make their way around differently and who learn at a different pace. The article delineates the mutual benefits of inclusivity and drives home the point that inclusive education in the Christian day school setting can be transformational for all involved.